The Evolution of Art and Design Pedagogies in England: Influences of the Past, Challenges for the Future. (13th June 2013) - Souleles, Nicos
<x xml:space="preserve">Abstract</x> This article traces the historical evolution of instructional methods in art and design education in Britain to identify the influences that inform current practices and compare the latter against recent debates on what are design education and designer in the context of the global economy and the widespread use of information and communication technologies (ICTs). This evolution starts in the thirteenth and fourteenth centuries with the master–apprentice model of learning on a one‐to‐one basis. Examination‐dominated teaching and didactic approaches prevailed up to the early twentieth century. In the latter part of the twentieth century, the entrance of art and design education into academia ushered gradual changes to pedagogy. The call for change has become more prominent in the context of the global knowledge economy.